An enquiry into the ideological coherence of black economic empowerment - Chard, David (My University, 2009)
Abstract Black Economic Empowerment (BEE) is an ambitious policy of the ANC-led South African (SA) government. The objectives of this far-reaching policy are outlined in the Broad-Based Black Economic Empowerment Act of 2003. This act, together with supporting policy and strategy documents, clearly indicates that BEE aims to achieve many and diverse objectives. These include: “achieving the constitutional right of equality; increasing participation of black people in the economy; promoting a higher growth rate; increased employment and more equitable income distribution”1. Analysing the ideological coherence of BEE requires a critical look at the competing ideological influences within the ANC, both contemporary and historical. The ANC’s commitment to an inclusive ideology of non-racialism has been a defining feature of the ANC, distinguishing the party from other factions of the liberation struggle. Although no reference is made to non-racialism in the Broad-Based BEE Act itself, ANC leaders frequently suggest that BEE is part of the ANC’s pursuit of a non-racial future. This report will highlight evidence of such claims and although such pronouncements were more prolific in ANC rhetoric in the 1990s, attention will also be drawn to the many recent references to this ideal in ANC documents and speeches. This contrasts with the enduring influence of African nationalism within the ANC. In examining the ideological foundations of BEE it is therefore essential that one trace the emergence of non-racial thinking within the ANC. This requires an investigation into the context in which non-racialism emerged, comparing and contrasting this ideology with the other ideological influences within the ANC. Such discussion will primarily focus on the competing influences of non-racialism and African nationalism, multi-racialism, and black consciousness. This examination will ultimately conclude that African nationalism has been the most enduring ideology within the ANC. The degree of inclusiveness in the ANC’s African nationalist thinking has shifted at various times, partly due to the influence of these other ideologies. This paper will argue that the current form approach to BEE reflects a shift towards a more exclusive form of African nationalism. 1 Broad-Based Black Economic Empowerment Act, 2003, Act No. 53, 2003